Microscopic Characterization of Keji Beling Extract (Strobilanthes crispus L.) As Herbal Medicine Studies - Pramita Laksitarahmi Isrianto; Sonny Kristianto; Sukian Wilujeng (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2021)
Keji Beling (Strobilanthes crispus L.) is one of medicinal plants in Acanthaceae family. The leaves are the part that is often used as the herbal products such as; herbs, tea and the others. This study aims to determine the characteristics of the functional groups of organic compounds, mineral content and antioxidant activity in the leaf extract of Strobilanthes crispus L. using pottery. Test analysis in research using FTIR, SEM-EDX, XRF. The result of showed the presence of CH alkenes, CH aromatic, C-O alcohol/ether/carboxylic acid/ester, C-N amine, NO2 Nitro compounds, O-H hydrogen bond alcohol /phenol and N-H amines/amides The mineral composition contained macro elements of Ca, K, P and S. While the identified micro minerals are Si, Fe, Mo, Sr, Mn, Ba, Cu, Zn, and Ni. The microscopic morphology of Strobilanthes crispus L. leaf extract is in the form of porous solid particels, thus it is to have high water solubility. The results of the antioxidant test using the DPPH method obtained an IC50 value of 19.20 ppm which is included in the group of very active antioxidants